ANALYSIS OF ECONOMIC CONJUNCTURE ON THE COLLECTION AND DISTRIBUTION OF ZAKAT, INFAQ, AND SADAQAH (ZIS) AND PROVINCIAL ECONOMIC GROWTH IN INDONESIA - Ramadhanty, Rifka Putri; Ryandono, Muhamad Nafik Hadi (Jurnal Ekonomi dan Bisnis Airlangga, 2025)
Introduction: This study analyzes the influence of macroeconomic factors—specifically inflation and unemployment—on the collection and distribution of zakat, as well as their impact on provincial economic growth in Indonesia. Methods: Data were collected from 33 provinces over the period 2012–2023. The study utilizes the path analysis model to process the collected data, employing SmartPLS 4.0 software for analytical procedures. Results: The study finds that inflation and unemployment negatively affect zakat collection and economic growth. Conversely, zakat collection has a positive influence on its distribution, which ultimately supports economic growth. Conclusion and suggestion: These findings underscore the potential of zakat as a macroeconomic instrument for sustainable development. The results provide important implications for zakat management and Islamic economic policy in Indonesia.